Cases in Corporate Governance - ROBERT WEARING (SAGE Publications, 2005)
Corporate governance is a fascinating subject which encompasses a number of diverse areas of study including management, finance and accounting as well as having implications for legal and political processes. This book intends to provide insights into current issues in corporate governance by examining the links between corporate governance theory, regulation and practice. The case studies contained in the book examine the circumstances of companies where corporate governance is seen to be an issue. An important feature of the book is the nine selected cases, some of which have been important in influencing codes and regulations of corporate behaviour in both the UK and the USA. The cases are designed to reinforce the reader’s understanding of the conditions under which corporate governance can break down and what is involved in trying to define ‘good’ corporate governance. In corporate governance there are not always ‘right’ and ‘wrong’ answers. Because of the nature of the topic there is never likely to be complete consensus on which system of governance is ideal under all possible circumstances and this aspect makes it an intriguing area for study. It is hoped that Cases in Corporate Governance will stimulate interest in the subject and encourage discussion of the various issues identified in the case studies.